Nutrigenomic study of germinated brown rice in type 2 diabetes mellitus - Imam, Mustapha Umar (2013)
Lifestyle factors, especially dietary, significantly affect the course of type 2 diabetes. The disease continues to debilitate millions around the world with significant impacts in the developing world. There are continuous efforts to curb this disease and despite considerable advances in its management, morbidity and mortality due to type 2 diabetes keep rising. As more evidence suggests events triggered by lifestyle factors cause significant impact on type 2 diabetes, there is a need for search of more alternatives to already available options for the effective management of this disease. Particularly, reports of its association with diets taken are now widely acknowledged, and with an increasing awareness of the role of diet in its etiopathogenesis,functional diets are being studied for their promising role. Consumption of white rice (WR) is one such factor especially in developing countries where it is used as a staple food. WR increases risk of diabetes and worsens it, and growing evidence now suggests germinated brown rice (GBR) to have potentials as a functional diet for managing this disease. The presence of bioactive compounds in GBR like γ-aminobutyric acid (GABA), γ-Oryzanol, dietary fibre, phenolics, vitamins, acylated steryl β-glucoside (ASG), and minerals confer functional properties including antihyperglycemia and antioxidative and hypocholesterolemic effects. In a type 2 diabetic rat model, induced by a combination of high fat diet and low dose streptozotocin injection (35 mg/kg body weight, dissolved in 100 mmol/l sodium citrate buffer, pH 4.5, injected intraperitoneally), effects of GBR, brown rice (BR) and WR in comparison to metformin were studied on fasting plasma glucose, lipid profile (total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglyceride), liver enzymes (alanine transaminase, γ-glutamyltranspeptidase and aspartate transaminase), serum urea and creatinine, hydroxyl radical scavenging activities of liver and kidneys, and plasma total antioxidant status. Nutrigenomic regulation of genes related to glucose metabolism, cholesterol metabolism, antioxidants and xenobiotic metabolism were equally evaluated to determine the effects of the different diets on transcriptional regulation of genes, as underlying mechanisms for the functional effects observed. Additionally, the contribution of individual bioactives (ASG, GABA, oryzanol and phenolics) towards such nutrigenomic mechanisms was evaluated using HEPG2 cells.BR and GBR reduced plasma glucose (9 % and 34 % reduction) more than metformin (3 %) while WR worsened glycemic control (28 % increase) over 4 weeks of intervention. Through nutrigenomic suppression, BR and GBR were shown to downregulate gluconeogenic genes (Fbp and Pck) in a similar manner to, but better than metformin, while WR upregulated the same genes. The fold changes in expression of the Fbp and Pck genes, for the WR, BR and GBR groups in comparison to diabetic untreated group, were 1.2, 0.5 and 0.4, and 1.2, 0.7 and 0.5, respectively. Also, upregulation of apolipoprotein A1 and low-density lipoprotein receptor genes were involved in GBR‘s hypocholesterolemic effects, with fold changes of 2.9 and 1.2, respectively, while the genes were upregulated in WR and BR groups by 1 fold. The bioactive compounds mostly produced similar patterns of effects on transcriptional regulation of the glucose- and cholesterol-metabolism genes in HEPG2 cells. This suggested that synergism due to the bioactive compounds may have contributed to the overall functional effects of GBR. Furthermore, GBR improved antioxidant status better than BR, WR and metformin. It improved total antioxidant status, and liver and kidney hydroxyl radical scavenging activities in type 2 diabetic rats, and also preserved their liver enzymes, as well as serum creatinine. Upregulation of the catalase and superoxide dismutase genes was shown to be involved in GBR‘s antioxidant effects. Also, synergistic effects of the different bioactive compounds likely contributed to the transcriptional regulation of the antioxidant genes. In HEPG2 cells, all bioactives upregulated SOD 2 gene in a dose dependent manner, while only GABA and oryzanol upregulated SOD 1 and catalase genes respectively. Also, upregulation of some xenobiotic metabolism genes in type 2 diabetic rats was potentiated by WR, with the likely consequence of faster drug metabolism, less drug efficacy and more toxicity. GBR did not produce as much upregulation as WR, and BR showed significantly lower expression values than both WR and GBR. Interestingly, the bioactive compounds in GBR upregulated the peroxisome proliferator activated receptor gamma (PPARγ), while in combination they downregulated the gene. The fact that GBR downregulates gluconeogenic genes (Fbp and Pck genes) similar to metformin, but has a better glycemic control in Type 2 diabetic rats, suggests other mechanisms are involved in GBR‘s antihyperglycemic properties. Also, upregulation of the genes studied here cannot be said to account for all GBR‘s hypocholesterolemic and antioxidant effects since bioactives in GBR are proven to have other transcriptional and non-transcriptional mechanisms for lowering cholesterol and improving antioxidant status. Potentially as data from the current study shows, multiple mechanisms of antihyperglycemic, hypocholesterolemic and antixodant effects could mean stricter control of metabolic indices by GBR. It could potentially provide enhancements in metabolic outcomes in type 2 diabetes mellitus better than metformin. Although, the data from the current findings are from chemically induced diabetes mellitus, there are other studies that have reported on GBR‘s effects on human diabetes. It appears that the findings from human studies mirror those of the current animal experiments and other closely related ones, suggesting that the current findings may likely be reproduced in humans also. If GBR replaces WR as the staple food of choice for 3 billion people around the world, the implications would be profound on the prevention of diabetic complications. This could effectively reduce burden of the disease especially in poor countries where there is limited access to expensive medications and state-of-the-art healthcare facilities. In view of these benefits and the chronic nature of diabetes, the antidiabetic properties of GBR are worth studying further on a long term basis, especially in humans.